2020
DOI: 10.1007/s00125-020-05302-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian hormone levels and risk of type 2 diabetes in women

Abstract: Aims/hypothesis Given its role in ovarian follicle development, circulating anti-Müllerian hormone (AMH) is considered to be a marker of reproductive ageing. Although accelerated reproductive ageing has been associated with a higher risk of type 2 diabetes, research on the relationship between AMH and type 2 diabetes risk is scarce. Therefore, we aimed to investigate whether age-specific AMH levels and age-related AMH trajectories are associated with type 2 diabetes risk in women. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…IGF2 [494], IRF7 [495], E2F1 [496], TEAD4 [497], KCNH2 [498], E2F2 [499], SNHG7 [500], FLI1 [501], CYP3A5 [502], HMGCS2 [503], GOT1 [504], PPARGC1A [505], GC (GC vitamin D binding protein) [506], VNN1 [507], NOX4 [508], SLC2A1 [509], BPGM (bisphosphoglyceratemutase) [164], NR4A3 [354], PFKFB2 [510], CDH2 [511], F11 [512], AQP2 [513], CLDN2 [514], EGF (epidermal growth factor) [515], ANGPT1 [516], KNG1 [517], SERPINA5 [518], HRG (histidine rich glycoprotein) [519], KL (klotho) [520], DEFB1 [521], ACE2 [522], AQP3 [523], CADM1 [188], DPP4 [524], STC1 [525], REN (renin) [526], TRPM6 [527], MSR1 [528], CCR1 [529], TNFRSF11B [530], FZD5 [531], ERBB4 [216], F8 [532], VCAM1 [533], PTGER3 [534] and ALB (albumin) [535] have been shown to influence the genetic risk of sepsis. IGF2 [536], IRF7 [100], PRKCB (protein kinase C beta) [101], CCL5 [537], EEF1A2 [538], ACTN3 [264], FCN1 [539], BRSK2 [540], MNX1 [541], AMH (anti-Mullerian hormone) [542], E2F1 [543], HAP1 [544], PF4 [545], AGER (advanced glycosylation end-product specific receptor) [546], E2F2 [547], TYMP (thymidine phosphorylase) [548], PPP1CC [549], NR2E1 [550], GREM1 [436], GRIN1 [551], WNT3A [552], COMP (cartilage oligomeric matrix protein) [553], BHMT (betaine--homocysteine S-methyltransferase) [554], ANGPTL3 [555], PCK1 [556], KMO (kynurenine 3-monooxygenase) [557], HSD11B2 […”
Section: Discussionmentioning
confidence: 99%
“…IGF2 [494], IRF7 [495], E2F1 [496], TEAD4 [497], KCNH2 [498], E2F2 [499], SNHG7 [500], FLI1 [501], CYP3A5 [502], HMGCS2 [503], GOT1 [504], PPARGC1A [505], GC (GC vitamin D binding protein) [506], VNN1 [507], NOX4 [508], SLC2A1 [509], BPGM (bisphosphoglyceratemutase) [164], NR4A3 [354], PFKFB2 [510], CDH2 [511], F11 [512], AQP2 [513], CLDN2 [514], EGF (epidermal growth factor) [515], ANGPT1 [516], KNG1 [517], SERPINA5 [518], HRG (histidine rich glycoprotein) [519], KL (klotho) [520], DEFB1 [521], ACE2 [522], AQP3 [523], CADM1 [188], DPP4 [524], STC1 [525], REN (renin) [526], TRPM6 [527], MSR1 [528], CCR1 [529], TNFRSF11B [530], FZD5 [531], ERBB4 [216], F8 [532], VCAM1 [533], PTGER3 [534] and ALB (albumin) [535] have been shown to influence the genetic risk of sepsis. IGF2 [536], IRF7 [100], PRKCB (protein kinase C beta) [101], CCL5 [537], EEF1A2 [538], ACTN3 [264], FCN1 [539], BRSK2 [540], MNX1 [541], AMH (anti-Mullerian hormone) [542], E2F1 [543], HAP1 [544], PF4 [545], AGER (advanced glycosylation end-product specific receptor) [546], E2F2 [547], TYMP (thymidine phosphorylase) [548], PPP1CC [549], NR2E1 [550], GREM1 [436], GRIN1 [551], WNT3A [552], COMP (cartilage oligomeric matrix protein) [553], BHMT (betaine--homocysteine S-methyltransferase) [554], ANGPTL3 [555], PCK1 [556], KMO (kynurenine 3-monooxygenase) [557], HSD11B2 […”
Section: Discussionmentioning
confidence: 99%
“…The samples were also taken within a narrow window of 20 days for the 1st trimester measurement and 34 days for the 2nd trimester measurement, therefore limiting the potential variability originating from differences in gestational age. The study population had limited heterogeneity as participants with PCOS or diabetes were excluded from this study, to make the data less susceptible to the effects of extreme outliers (Al Khafaji et al, 2017, Kim et al, 2016, Bhattacharya et al, 2022, Teede et al, 2019, Verdiesen et al, 2021. As such, these results cannot be generalised to women with PCOS or diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating AMH was well known to be play important role in ovarian follicle development and was considered to be a marker of reproductive ageing. Recent epidemiological investigation was surveyed in 3293 female participants and it was observed that lower age-specific AMH levels were associated with a higher risk of type 2 diabetes in women [22]. However, whether AMH is involved in part of the pathological process of IR remains unclear.…”
Section: Discussionmentioning
confidence: 99%